Ability to Keep Milk-Ejecting Activity after Premature Birth - S. G. Gribakin; O. L. Lukoyanova; T. E. Borovik; I. N. Zakharova; V. A. Skvortsova (Вопросы современной педиатрии, 2015)
The article examines the modern data on the importance of breast milk in nursing premature babies. It is shown that the amount of breast milk in women, who gave birth prematurely, decreases rapidly, especially when it is impossible to get a baby latched on to the breast. There is a negative correlation between gestational age and duration of lactation. According to the opinion of both doctors and the majority of mothers, pumping out breast milk and using it in feeding a premature baby is an important psychological and physiological factor linking a mother and a child at the intensive care unit. Individual breast milk banks are a new safe and effective method for long-term keeping of breast milk.